Modeling of budget spending of Donetsk region - Sokolovska, O.V.; Sokolovskyi, D.B. (Економіка промисловості, 2014)
In current Ukrainian forecasting practice budget expenditures are often planned according to achieved results, taking into account the inflation rate. But this principle does not allow defining medium- and long-term trends, which provides evidence of lack of adequate forecasting of local budget expenditures. Now the scientifically-based approach toforecast local budget expenditures is required; the latest is impossible without using of mathematical and economic models. Given paper is aimed to develop scientifically based methods and models in order to forecast local budget expenditures and to make a medium-term forecast of local budget expenditures for Donetsk region. In order to choice an appropriate forecasting model, based on existing theoretical issues, we distinguished three classes of forecasting models: microsimulation models, component-based models, regional-level models. This analysis allowed us to determine the forecasting technique which is the mixed variant of deterministic and econometric models. It based on using of correlatable factors, which influence directly on benchmark parameter - budget expenditures. Such technique provides the medium-term forecasting of budget expenditures in Donetsk region for 2014-2016. Input model data includes official statistical data for all considering indexes and also for benchmark parameter, covering period 2006- 2013, by half-year. After preliminary estimates we’ve chosen two forecasting models of multivariate regression type: additive and multiplicative (logarithmic) models. Modeling results showed that ratio between budget expenditures in Donets region and Ukraine’s GDP is sufficiently stable, it changes continuously according to political and economical government decisions; the saccadic changes can be naturally explained by hypothesis of external pulse effects (as it was in the second half of 2008). The chosen models allowed us to make a medium-term forecast of local budget expenditures of Donetsk region. Results of forecasting, as well as analytical conclusions can be useful for budget management in Donetsk region. Developed mathematical economic models can be used to forecast spending of local budgets of Ukraine. Розглянуто науково обґрунтовану пропозицію методів і моделей прогнозування видатків місцевих бюджетів. Серед інших обрано дві найбільш адекватні моделі багатовимірної регресії: адитивну та мультиплікативну. Порівняння результатів показало, що обидві моделі досить точно і приблизно однаково апроксимують вихідні дані. За їх допомоги здійснено прогноз бюджетних видатків на середньострокову перспективу для Донецької області. Рассмотрено научно обоснованное предложение методов и моделей прогнозирования расходов местных бюджетов. Среди прочих выбраны две наиболее адекватные модели многомерной регрессии: аддитивная и мультипликативная. Сопоставление результатов показало, что обе модели достаточно точно и примерно одинаково аппроксимируют выходные данные. С их помощью осуществлён прогноз бюджетных расходов на среднесрочную перспективу для Донецкой области.